A high-toughness tensile PE material and preparation method thereof
Through the hydroxidization and modification of nano -nanotoxide, combined with the co -mixing and melting extrusion process of polyethylene resin to prepare high -tough tensile PE materials, solve the insufficient toughness and tensile degree of polyethylene materials in the packaging bags. The problem realizes the excellent toughness and tensile strength of the material, and the effect of decreased slowly after aging.
Patent Information
- Application Number
- CN202410723161.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-05
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-06-05
AI Technical Summary
Polyethylene materials have problems such as insufficient toughness and insufficient tensile resistance in clothing packaging bags, which are prone to tear or tear due to environmental stress, and cannot effectively play the role of packaging and sealing.
The hydroxygenization is performed by the nano -nanotoxide, and the use of dual -key sirrius coupling agents and acrylamide and other materials are used for modification to form organic modification fillers. Material.
The prepared PE material has excellent toughness and tensile strength in actual use, and its toughness decreases slowly after accelerated aging testing, significantly improving the durability of the material.
Smart Images

Figure BDA0004877812450000121 
Figure BDA0004877812450000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyethylene, and in particular relates to a high-toughness tensile-resistant PE material and a preparation method thereof. Background Art
[0002] Polyethylene, abbreviated as PE, is a thermoplastic resin made from ethylene monomers through polymerization. It has excellent low-temperature resistance, good chemical stability, and resistance to corrosion by most acids and alkalis. It is widely used in the fields of wires and cables, pipes, containers, and packaging materials. Among them, most packaging bags for clothing are made of polyethylene as the base resin. It can be seen that it plays a vital role in human daily life. However, since polyethylene materials are more sensitive to environmental stress, this leads to problems such as insufficient toughness and insufficient tensile strength when it is actually used in clothing packaging bags. It is very easy for the packaging bags to be torn or ripped due to environmental stress, and cannot play the role well. Some packaging and sealing functions, and in order to solve this technical defect, many existing technologies will add inorganic nanoparticles to polyethylene materials to achieve the purpose of toughening and enhancing tensile strength. However, these existing technologies still have many disadvantages that limit their actual effects. This is because on the one hand, the dispersibility of inorganic nanoparticles in organic polymer systems is poor, and agglomeration is very likely to occur, which causes the toughening and enhancing tensile strength to become very limited. On the other hand, inorganic nanoparticles cannot effectively and efficiently alleviate the aging phenomenon of polyethylene products caused by a large amount of light, heat, oxygen, radiation, etc. during daily use. As the use time goes by, the aging phenomenon will become more and more obvious, and the toughness will be greatly reduced. Summary of the invention
[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a high-toughness tensile PE material and a preparation method thereof. The present invention creatively performs hydroxylation treatment on nano-silicon dioxide to enrich its surface with more active hydroxyl groups, then uses a double-bond silane coupling agent to perform dehydration condensation of alkoxy groups and hydroxyl groups to modify the double bonds, then uses acrylamide as a polymerization monomer to open the double bonds to form a polymer-modified structure, and finally adds a chlorinated antioxidant obtained by replacing the carboxyl hydroxyl groups in 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid with chlorine atoms to perform condensation of acyl chloride and amino groups, thereby preparing an organic modified filler, so that the PE material obtained by melt-extruding the PE material with a polyethylene resin has excellent toughness and tensile strength when actually used, and on the other hand, after accelerated aging test, its toughness also decreases very slowly.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a high-toughness tensile PE material, the preparation method comprising the following steps:
[0006] (1) mixing polyethylene resin and organic modified filler at 65-80° C. for 5-10 minutes to obtain a mixed material;
[0007] (2) The mixed material is conveyed to a twin-screw extruder for extrusion granulation, and the preparation is completed.
[0008] As a preferred technical solution of the present invention, the polyethylene resin in step (1) is at least one of a high-density polyethylene resin, a low-density polyethylene resin and a linear low-density polyethylene resin.
[0009] As a preferred technical solution of the present invention, the polyethylene resin in step (1) is purchased directly from the market.
[0010] As a preferred technical solution of the present invention, the organic modified filler in step (1) is prepared by the following steps:
[0011] Step A: adding 25-30 parts by weight of hydrogen peroxide and 5-6 parts by weight of nano-silicon dioxide to 60-70 parts by weight of concentrated sulfuric acid, stirring at 70-80° C. for 1-2 hours, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 70-80° C. until constant weight, to obtain hydroxylated nano-silicon dioxide;
[0012] Step B: adding the hydroxylated nano-silica, 1-1.5 parts by weight of a double-bond silane coupling agent and 0.1-0.2 parts by weight of deionized water to 80-100 parts by weight of anhydrous ethanol, stirring at 65-70° C. for 24-26 hours, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 70-80° C. until constant weight, to obtain double-bond modified nano-silica;
[0013] Step C: adding the double bond modified nano-silica and 0.2-0.3 parts by weight of ammonium persulfate to 60-80 parts by weight of deionized water, stirring for 5-10 minutes at room temperature, then adding 4-6 parts by weight of acrylamide, stirring for 5-6 hours at 60-65° C., filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 70-80° C. until constant weight, to obtain polymer modified nano-silica;
[0014] Step D: adding 2-3 parts by weight of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 5-7 parts by weight of thionyl chloride to 50-60 parts by weight of dichloromethane, stirring at room temperature for 4-5 hours under a nitrogen atmosphere, and finally distilling under reduced pressure to obtain a chlorinated antioxidant;
[0015] Step E: Add the chlorinated antioxidant, the polymer-modified nano-silica and 1-2 parts by weight of triethylamine to 80-100 parts by weight of toluene, then stir at 70-90° C. for 45-50 hours under a nitrogen atmosphere, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 70-80° C. until constant weight, and the preparation is completed.
[0016] Furthermore, the mass fraction of the concentrated sulfuric acid in step A is 70-75%.
[0017] Furthermore, the particle size of the nano-silicon dioxide in step A is 10-50 nm.
[0018] Furthermore, the double bond silane coupling agent in step B is at least one of vinyl trimethoxy silane and vinyl triethoxy silane.
[0019] Furthermore, the flow rate of the nitrogen atmosphere in step D is 150-200 mL / min.
[0020] Furthermore, the reduced pressure distillation in step D refers to distillation at 25-30° C. under a vacuum degree of -0.1 MPa until the volatiles are completely removed.
[0021] Furthermore, the flow rate of the nitrogen atmosphere in step E is 150-200 mL / min.
[0022] As a preferred technical solution of the present invention, the weight ratio of the polyethylene resin to the organic modified filler in step (1) is 90-100:5-7.
[0023] As a preferred technical solution of the present invention, the operating parameters of the twin-screw extruder in step (2) are as follows: the temperature of zone 1 is controlled at 130-135°C, the temperature of zone 2 is controlled at 135-140°C, the temperature of zone 3 is controlled at 145°C, the temperature of zone 4 is controlled at 150°C, the rotation speed is controlled at 150-200rpm, and the feeding rate is controlled at 20-25kg / h.
[0024] A high-toughness tensile PE material prepared by the preparation method as described above.
[0025] Beneficial effects of the present invention:
[0026] (1) The present invention creatively performs hydroxylation treatment on nano-silica to enrich its surface with more active hydroxyl groups, then uses a double-bond silane coupling agent to perform dehydration condensation of alkoxy groups and hydroxyl groups to modify the double bonds, then uses acrylamide as a polymerization monomer to open the double bonds to form a polymer-modified structure, and finally adds a chlorinated antioxidant obtained by replacing the carboxyl hydroxyl groups in 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid with chlorine atoms to perform condensation of acyl chloride and amino groups, thereby preparing an organic modified filler, which is used to prepare a PE material obtained by melt extrusion with a polyethylene resin. When actually used, on the one hand, it has excellent toughness and tensile strength, and on the other hand, after accelerated aging test, its toughness also decreases very slowly.
[0027] (2) The present invention creatively prepares an organic modified filler, and blends and melt-extrudes it with a polyethylene resin to obtain a PE material. Since the surface of the organic modified filler is a structure modified by an organic polymer, it can have very good compatibility with the polyethylene resin, which is also an organic polymer, and improves its dispersion ability. It is not easy to agglomerate, and can better play the role of toughening and enhancing tensile strength. At the same time, the structure modified by the organic polymer can also produce a strong entanglement and entanglement effect with the molecular chain of the polyethylene resin, so that the interfacial bonding force between the two phases is further strengthened, thereby improving the energy conversion efficiency between the two phases when subjected to stress, and can better consume energy through the plastic deformation of the polyethylene resin, thereby promoting the improvement of its toughness and tensile strength. In addition, the structure of the organic polymer also contains phenolic hydroxyl groups, which can capture various free radicals generated during the aging process, thereby slowing down aging and slowing down the decline of toughness. Compared with the prior art, the probability of the present invention using phenolic hydroxyl groups to capture various free radicals can be improved by relying on the entanglement and entanglement of molecular chains, and can better play the anti-aging effect.
[0028] (3) The present invention creatively performs hydroxylation treatment on nano-silica first, so that its surface is rich in more active hydroxyl groups, thereby providing more active sites for various subsequent modification treatments, and finally endowing the prepared PE material with excellent toughness and tensile properties through the action of organic modified fillers. DETAILED DESCRIPTION
[0029] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0030] The polyethylene resins in all the embodiments and comparative examples of the present invention were purchased directly from the market, purchased from Beijing Yanshan Petrochemical Co., Ltd., with a brand of 5000S; the nano-silicon dioxide was purchased directly from the market, purchased from Nanjing Baoket New Materials Co., Ltd., with a product model of PST-G02.
[0031] Example 1
[0032] A method for preparing a high-toughness tensile PE material, the preparation method comprising the following steps:
[0033] (1) stirring and mixing the polyethylene resin and the organic modified filler at 65° C. for 5 minutes to obtain a mixed material;
[0034] (2) The mixed material is conveyed to a twin-screw extruder for extrusion granulation, and the preparation is completed.
[0035] The polyethylene resin in step (1) is a high-density polyethylene resin.
[0036] The polyethylene resin in step (1) is directly purchased from the market.
[0037] The organic modified filler in step (1) is prepared by the following steps:
[0038] Step A: adding 25 parts by weight of hydrogen peroxide and 5 parts by weight of nano-silicon dioxide to 60 parts by weight of concentrated sulfuric acid, stirring at 70° C. for 1 hour, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 70° C. until constant weight, to obtain hydroxylated nano-silicon dioxide;
[0039] Step B: adding the hydroxylated nano-silica, 1 part by weight of a double-bond silane coupling agent and 0.1 part by weight of deionized water to 80 parts by weight of anhydrous ethanol, stirring at 65° C. for 24 hours, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 70° C. until constant weight, to obtain double-bond modified nano-silica;
[0040] Step C: adding the double bond modified nano-silica and 0.2 parts by weight of ammonium persulfate to 60 parts by weight of deionized water, stirring for 5 minutes at room temperature, then adding 4 parts by weight of acrylamide, stirring for 5 hours at 60° C., filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 70° C. until constant weight, to obtain polymer modified nano-silica;
[0041] Step D: Add 2 parts by weight of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 5 parts by weight of thionyl chloride to 50 parts by weight of dichloromethane, then stir at room temperature for 4 hours under a nitrogen atmosphere, and finally distill under reduced pressure to obtain a chlorinated antioxidant;
[0042] Step E: Add the chlorinated antioxidant, the polymer-modified nano-silica and 1 part by weight of triethylamine to 80 parts by weight of toluene, then stir at 70° C. for 45 hours under a nitrogen atmosphere, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 70° C. until constant weight, and the preparation is completed.
[0043] The mass fraction of concentrated sulfuric acid in step A is 70%.
[0044] The particle size of the nano-silicon dioxide in step A is 20 nm.
[0045] The double bond silane coupling agent in step B is vinyltrimethoxysilane.
[0046] The flow rate of the nitrogen atmosphere in step D is 150 mL / min.
[0047] The reduced pressure distillation in step D refers to distillation at 30° C. under a vacuum degree of −0.1 MPa until the volatiles are completely removed.
[0048] The flow rate of the nitrogen atmosphere in step E is 150 mL / min.
[0049] The weight ratio of the polyethylene resin to the organic modified filler in step (1) is 90:5.
[0050] The operating parameters of the twin-screw extruder in step (2) are as follows: the temperature of zone 1 is controlled at 130°C, the temperature of zone 2 is controlled at 135°C, the temperature of zone 3 is controlled at 145°C, the temperature of zone 4 is controlled at 150°C, the rotation speed is controlled at 150rpm, and the feeding rate is controlled at 20kg / h.
[0051] A high-toughness tensile PE material prepared by the preparation method as described above.
[0052] Example 2
[0053] A method for preparing a high-toughness tensile PE material, the preparation method comprising the following steps:
[0054] (1) mixing the polyethylene resin and the organic modified filler at 80° C. for 10 minutes to obtain a mixed material;
[0055] (2) The mixed material is conveyed to a twin-screw extruder for extrusion granulation, and the preparation is completed.
[0056] The polyethylene resin in step (1) is a high-density polyethylene resin.
[0057] The polyethylene resin in step (1) is directly purchased from the market.
[0058] The organic modified filler in step (1) is prepared by the following steps:
[0059] Step A: adding 30 parts by weight of hydrogen peroxide and 6 parts by weight of nano-silicon dioxide to 70 parts by weight of concentrated sulfuric acid, stirring at 80° C. for 2 hours, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 80° C. until constant weight, to obtain hydroxylated nano-silicon dioxide;
[0060] Step B: adding the hydroxylated nano-silica, 1.5 parts by weight of a double-bond silane coupling agent and 0.2 parts by weight of deionized water to 100 parts by weight of anhydrous ethanol, stirring at 70° C. for 26 hours, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 80° C. until constant weight, to obtain double-bond modified nano-silica;
[0061] Step C: adding the double bond modified nano-silica and 0.3 parts by weight of ammonium persulfate to 80 parts by weight of deionized water, stirring for 10 minutes at room temperature, then adding 6 parts by weight of acrylamide, stirring for 6 hours at 65° C., filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 80° C. until constant weight, to obtain polymer modified nano-silica;
[0062] Step D: adding 3 parts by weight of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 7 parts by weight of thionyl chloride to 60 parts by weight of dichloromethane, stirring at room temperature for 5 hours under a nitrogen atmosphere, and finally distilling under reduced pressure to obtain a chlorinated antioxidant;
[0063] Step E: Add the chlorinated antioxidant, the polymer-modified nano-silica and 2 parts by weight of triethylamine to 100 parts by weight of toluene, then stir at 90° C. for 50 hours under a nitrogen atmosphere, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 80° C. until constant weight, and the preparation is completed.
[0064] The mass fraction of concentrated sulfuric acid in step A is 75%.
[0065] The particle size of the nano-silicon dioxide in step A is 20 nm.
[0066] The double bond silane coupling agent in step B is vinyltrimethoxysilane.
[0067] The flow rate of the nitrogen atmosphere in step D is 200 mL / min.
[0068] The reduced pressure distillation in step D refers to distillation at 30° C. under a vacuum degree of −0.1 MPa until the volatiles are completely removed.
[0069] The flow rate of the nitrogen atmosphere in step E is 200 mL / min.
[0070] The weight ratio of the polyethylene resin to the organic modified filler in step (1) is 100:7.
[0071] The operating parameters of the twin-screw extruder in step (2) are as follows: the temperature of zone 1 is controlled at 135°C, the temperature of zone 2 is controlled at 140°C, the temperature of zone 3 is controlled at 145°C, the temperature of zone 4 is controlled at 150°C, the rotation speed is controlled at 200rpm, and the feeding rate is controlled at 25kg / h.
[0072] A high-toughness tensile PE material prepared by the preparation method as described above.
[0073] Example 3
[0074] A method for preparing a high-toughness tensile PE material, the preparation method comprising the following steps:
[0075] (1) mixing the polyethylene resin and the organic modified filler at 75° C. for 8 minutes to obtain a mixed material;
[0076] (2) The mixed material is conveyed to a twin-screw extruder for extrusion granulation, and the preparation is completed.
[0077] The polyethylene resin in step (1) is a high-density polyethylene resin.
[0078] The polyethylene resin in step (1) is directly purchased from the market.
[0079] The organic modified filler in step (1) is prepared by the following steps:
[0080] Step A: adding 28 parts by weight of hydrogen peroxide and 5.5 parts by weight of nano-silicon dioxide to 65 parts by weight of concentrated sulfuric acid, stirring at 75° C. for 1.5 hours, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 75° C. until constant weight, to obtain hydroxylated nano-silicon dioxide;
[0081] Step B: adding the hydroxylated nano-silica, 1.3 parts by weight of a double-bond silane coupling agent and 0.15 parts by weight of deionized water to 90 parts by weight of anhydrous ethanol, stirring at 68° C. for 25 hours, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 75° C. until constant weight, to obtain double-bond modified nano-silica;
[0082] Step C: adding the double bond modified nano-silica and 0.25 parts by weight of ammonium persulfate to 70 parts by weight of deionized water, stirring at room temperature for 8 minutes, then adding 5 parts by weight of acrylamide, stirring at 63° C. for 5.5 hours, filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 75° C. until constant weight, to obtain polymer modified nano-silica;
[0083] Step D: Add 2.5 parts by weight of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 6 parts by weight of thionyl chloride to 55 parts by weight of dichloromethane, then stir at room temperature for 4.5 hours under a nitrogen atmosphere, and finally distill under reduced pressure to obtain a chlorinated antioxidant;
[0084] Step E: Add the chlorinated antioxidant, the polymer-modified nano-silica and 1.5 parts by weight of triethylamine to 90 parts by weight of toluene, then stir at 80° C. for 46 hours under a nitrogen atmosphere, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 75° C. until constant weight, and the preparation is completed.
[0085] The mass fraction of concentrated sulfuric acid in step A is 73%.
[0086] The particle size of the nano-silicon dioxide in step A is 20 nm.
[0087] The double bond silane coupling agent in step B is vinyltrimethoxysilane.
[0088] The flow rate of the nitrogen atmosphere in step D is 180 mL / min.
[0089] The reduced pressure distillation in step D refers to distillation at 30° C. under a vacuum degree of −0.1 MPa until the volatiles are completely removed.
[0090] The flow rate of the nitrogen atmosphere in step E is 180 mL / min.
[0091] The weight ratio of the polyethylene resin to the organic modified filler in step (1) is 95:6.
[0092] The operating parameters of the twin-screw extruder in step (2) are as follows: the temperature of zone 1 is controlled at 133°C, the temperature of zone 2 is controlled at 138°C, the temperature of zone 3 is controlled at 145°C, the temperature of zone 4 is controlled at 150°C, the rotation speed is controlled at 180rpm, and the feeding rate is controlled at 23kg / h.
[0093] A high-toughness tensile PE material prepared by the preparation method as described above.
[0094] Comparative Example 1
[0095] Based on Example 1, step D and step E are not performed, and the rest remain unchanged.
[0096] Comparative Example 2
[0097] On the basis of Example 1, step C, step D and step E are not performed, and the rest remain unchanged.
[0098] Comparative Example 3
[0099] On the basis of Example 1, step A is omitted, the hydroxylated nano-silica in step B is replaced with nano-silica with a particle size of 20 nm, and the rest remain unchanged.
[0100] Comparative Example 4
[0101] On the basis of Example 1, step D and step E are not performed, and step (1) is changed to mixing the polyethylene resin, the organic modified filler and the 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid at 65° C. for 5 min to obtain a mixed material; the amount ratio of the organic modified filler to the 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is 5:2; and the rest remain unchanged.
[0102] Comparative Example 5
[0103] A method for preparing a high-toughness tensile PE material, the preparation method comprising the following steps:
[0104] (1) stirring and mixing the polyethylene resin and the organic modified filler at 65° C. for 5 minutes to obtain a mixed material;
[0105] (2) The mixed material is conveyed to a twin-screw extruder for extrusion granulation, and the preparation is completed.
[0106] The polyethylene resin in step (1) is a high-density polyethylene resin.
[0107] The polyethylene resin in step (1) is directly purchased from the market.
[0108] The organic modified filler in step (1) is prepared by the following steps:
[0109] Step A: adding 25 parts by weight of hydrogen peroxide and 5 parts by weight of nano-silicon dioxide to 60 parts by weight of concentrated sulfuric acid, stirring at 70° C. for 1 hour, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 70° C. until constant weight, to obtain hydroxylated nano-silicon dioxide;
[0110] Step B: adding the hydroxylated nano-silica, 1 part by weight of a double bond silane coupling agent, 0.5 part by weight of an aminosilane coupling agent and 0.1 part by weight of deionized water to 80 parts by weight of anhydrous ethanol, stirring at 65° C. for 24 hours, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 70° C. until constant weight, to obtain double bond and amino modified nano-silica;
[0111] Step C: adding 2 parts by weight of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 5 parts by weight of thionyl chloride to 50 parts by weight of dichloromethane, stirring at room temperature for 4 hours under a nitrogen atmosphere, and finally distilling under reduced pressure to obtain a chlorinated antioxidant;
[0112] Step D: adding the chlorinated antioxidant, the double bond and amino modified nano-silica and 1 part by weight of triethylamine to 80 parts by weight of toluene, stirring at 70° C. for 45 hours under a nitrogen atmosphere, filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 70° C. until constant weight, to obtain double bond and antioxidant modified nano-silica;
[0113] Step E: Add the double bond and antioxidant modified nano-silica and 0.2 parts by weight of ammonium persulfate to 60 parts by weight of deionized water, stir and mix at room temperature for 5 minutes, then add 4 parts by weight of acrylamide, stir at 60°C for 5 hours, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 70°C until constant weight, and the preparation is completed.
[0114] The mass fraction of concentrated sulfuric acid in step A is 70%.
[0115] The particle size of the nano-silicon dioxide in step A is 20 nm.
[0116] The double bond silane coupling agent in step B is vinyltrimethoxysilane.
[0117] The aminosilane coupling agent in step B is γ-aminopropyltrimethoxysilane.
[0118] The flow rate of the nitrogen atmosphere in step C is 150 mL / min.
[0119] The reduced pressure distillation in step C refers to distillation at 30° C. under a vacuum degree of -0.1 MPa until the volatiles are completely removed.
[0120] The flow rate of the nitrogen atmosphere in step D is 150 mL / min.
[0121] The weight ratio of the polyethylene resin to the organic modified filler in step (1) is 90:5.
[0122] The operating parameters of the twin-screw extruder in step (2) are as follows: the temperature of zone 1 is controlled at 130°C, the temperature of zone 2 is controlled at 135°C, the temperature of zone 3 is controlled at 145°C, the temperature of zone 4 is controlled at 150°C, the rotation speed is controlled at 150rpm, and the feeding rate is controlled at 20kg / h.
[0123] A high-toughness tensile PE material prepared by the preparation method as described above.
[0124] Comparative Example 6
[0125] On the basis of Example 1, the organic modified filler in step (1) was changed to nano-silicon dioxide with a particle size of 20 nm, and the rest remained unchanged.
[0126] Test Example 1
[0127] Toughness and tensile tests:
[0128] The high-toughness tensile PE materials prepared in Examples 1-3 and Comparative Examples 1-6 were respectively injection molded to obtain corresponding test objects (all with dimensions of 100 mm*10 mm*5 mm), wherein the temperature of the injection mold was 60°C, the injection temperature was 165°C, and the injection pressure was 0.25 MPa, and then toughness and tensile tests were performed:
[0129] Toughness test: The notched specimen cantilever beam impact strength is tested according to standard GB / T 1843-1996 to illustrate the toughness.
[0130] Tensile test: The tensile strength is tested according to the standard GB / T 1040.1-2006 to illustrate the tensile effect.
[0131] Table 1. Toughness and tensile test results
[0132]
[0133]
[0134] Test Example 2
[0135] Accelerated aging test:
[0136] The test object described in Test Example 1 was first heated in a constant temperature forced air oven at 90° C. for 48 h, naturally cooled to room temperature, and then subjected to a toughness test according to the description of Test Example 1.
[0137] Table 2. Accelerated aging test results
[0138] <![CDATA[Notched specimen Izod impact strength / KJ / m 2 > Example 1 68.7 Example 2 70.5 Example 3 68.9 Comparative Example 1 60.8 Comparative Example 2 56.0 Comparative Example 3 61.7 Comparative Example 4 65.8 Comparative Example 5 65.9 Comparative Example 6 39.0
[0139] Comparison between Example 1 and Comparative Examples 1-6 shows that:
[0140] The difference between Comparative Example 1 and Example 1 is that the organic modified filler is polymer modified nano-silica.
[0141] The difference between Comparative Example 2 and Example 1 is that the organic modified filler is double bond modified nano-silica.
[0142] The difference between Comparative Example 3 and Example 1 is that no hydroxylation treatment is performed.
[0143] The difference between Comparative Example 4 and Example 1 is that 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is not bonded to the organic modified filler, but is added to the system in a blended form.
[0144] The difference between Comparative Example 5 and Example 1 is that 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is not bonded to the polymer structure of the organic modified filler, but is still bonded to the organic modified filler.
[0145] The difference between Comparative Example 6 and Example 1 is that the organic modified filler is replaced by nano-silicon dioxide.
[0146] From the comparison between Example 1 and Comparative Examples 1-6 in Test Example 1, it can be seen that the high-toughness tensile PE material prepared by the present invention has excellent toughness and tensile effects.
[0147] From the comparison between Example 1 and Comparative Examples 1-6 in Test Example 2, it can be seen that the toughness of the high-toughness tensile PE material prepared by the present invention decreases very slowly and with a small drop even after accelerated aging.
[0148] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-toughness tensile PE material, characterized in that: The preparation method comprises the following steps: (1) mixing polyethylene resin and organic modified filler at 65-80° C. for 5-10 minutes to obtain a mixed material; (2) conveying the mixed material to a twin-screw extruder for extrusion granulation, and the preparation is completed; The organic modified filler in step (1) is prepared by the following steps: Step A: adding 25-30 parts by weight of hydrogen peroxide and 5-6 parts by weight of nano-silicon dioxide to 60-70 parts by weight of concentrated sulfuric acid, stirring at 70-80° C. for 1-2 hours, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 70-80° C. until constant weight, to obtain hydroxylated nano-silicon dioxide; Step B: adding the hydroxylated nano-silica, 1-1.5 parts by weight of a double-bond silane coupling agent and 0.1-0.2 parts by weight of deionized water to 80-100 parts by weight of anhydrous ethanol, stirring at 65-70° C. for 24-26 hours, filtering, removing the filtrate, washing with anhydrous ethanol, and finally vacuum drying at 70-80° C. until constant weight, to obtain double-bond modified nano-silica; Step C: adding the double bond modified nano-silica and 0.2-0.3 parts by weight of ammonium persulfate to 60-80 parts by weight of deionized water, stirring for 5-10 minutes at room temperature, then adding 4-6 parts by weight of acrylamide, stirring for 5-6 hours at 60-65° C., filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 70-80° C. until constant weight, to obtain polymer modified nano-silica; Step D: adding 2-3 parts by weight of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 5-7 parts by weight of thionyl chloride to 50-60 parts by weight of dichloromethane, stirring at room temperature for 4-5 hours under a nitrogen atmosphere, and finally distilling under reduced pressure to obtain a chlorinated antioxidant; Step E: Add the chlorinated antioxidant, the polymer-modified nano-silica and 1-2 parts by weight of triethylamine to 80-100 parts by weight of toluene, then stir at 70-90° C. for 45-50 hours under a nitrogen atmosphere, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 70-80° C. until constant weight, and the preparation is completed.
2. The method for preparing a high-toughness tensile PE material according to claim 1, characterized in that: The polyethylene resin in step (1) is at least one of a high-density polyethylene resin, a low-density polyethylene resin and a linear low-density polyethylene resin.
3. The method for preparing a high-toughness tensile PE material according to claim 1, characterized in that: The polyethylene resin in step (1) is directly purchased from the market.
4. The method for preparing a high-toughness tensile PE material according to claim 1, characterized in that: The mass fraction of the concentrated sulfuric acid in step A is 70-75%.
5. The method for preparing a high-toughness tensile PE material according to claim 1, characterized in that: The particle size of the nano silicon dioxide in step A is 10-50 nm.
6. The method for preparing a high-toughness tensile PE material according to claim 1, characterized in that: The double bond silane coupling agent in step B is at least one of vinyl trimethoxy silane and vinyl triethoxy silane.
7. The method for preparing a high-toughness tensile PE material according to claim 1, characterized in that: The weight ratio of the polyethylene resin to the organic modified filler in step (1) is 90-100:5-7.
8. The method for preparing a high-toughness tensile PE material according to claim 1, characterized in that: The operating parameters of the twin-screw extruder in step (2) are as follows: the temperature of zone 1 is controlled at 130-135°C, the temperature of zone 2 is controlled at 135-140°C, the temperature of zone 3 is controlled at 145°C, the temperature of zone 4 is controlled at 150°C, the rotation speed is controlled at 150-200rpm, and the feeding rate is controlled at 20-25kg / h.
9. A high-toughness tensile PE material prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Modified high-density polyethylene resin for pipe materials, and preparation method thereof
CN107189182A